Helicobacter pylori eradication improves the quality of life regardless of the treatment outcome: A multicenter prospective cohort study. Issue 52 (December 2017) - Taguchi, Hiroki; Kanmura, Shuji; Maeda, Takuro; Iwaya, Hiromichi; Arima, Shiho; Sasaki, Fumisato; Nasu, Yuichirou; Tanoue, Shiroh; Hashimoto, Shinichi; Ido, Akio
Abstract : Abstract: Helicobacter pylori (Hp) eradication is recommended for improving the quality of life (QOL) of patients with epigastric symptoms, especially reflux and dyspepsia. However, no reports have investigated the improvement of QOL after the eradication of Hp irrespective of epigastric symptoms. The aim of this study was to investigate the improvement in the QOL after the eradication of Hp irrespective of epigastric symptoms, and evaluate the factors associated with an improved QOL after the eradication of Hp. This prospective cohort study was performed at 15 referral institutions from September 2013 to December 2014. The patients' QOL and epigastric symptoms were evaluated before and after the eradication of Hp using the 8-item Short-Form Health Survey (SF-8) and the modified Frequency Scale for the Symptoms of Gastroesophageal Reflux Disease, respectively. One hundred sixty-five of 184 Hp-infected patients underwent Hp eradication treatment. The treatment was successful in 82.4% (136/165) of the cases. One hundred sixty of the 165 Hp-infected patients were eligible for inclusion in the QOL analysis. In the indices of QOL on the SF-8, the scores on both the mental component summary (MCS) and the physical component summary (PCS) were found to have significantly improved after the eradication of Hp. However, the epigastric symptoms before the eradication of Hp were not correlated with either the MCS or PCS. A low QOL value before the eradication of Hp was the factor what was most strongly associated with the improvement in the QOL. The eradication of Hp improved the QOL, regardless of the outcome of the treatment, especially in patients who had an impaired QOL before the eradication.